Analisis Perhitungan Harga Pokok Produksi Menggunakan Metode Full Costing pada UMKM Warung Tongseng Pak Tolib di Kemanggisan: Analysis of the Calculation of the Cost of Production Using the Full Costing Method at MSMEs at Warung Tongseng Pak Tolib in Kemanggisan - Dita Adisti; Qori Qotrun Nada; Sopia Alpina; Syafitri Syafitri; Nazwa Asshafiyyah (PT Cakrawarti Empat Proksi, 2026)
The rapid development of the culinary world of MSMEs requires entrepreneurs to set appropriate selling prices to remain competitive and achieve maximum profits. One important factor in determining selling prices is accuracy in calculating the Cost of Goods Sold (COGS). This study aims to analyze the calculation of COGS using the Full Costing method at the MSME Warung Tongseng Pak Tolib located in Kemanggisan and to determine the differences between the calculation results by business actors and the Full Costing method. The approach used in this study is descriptive quantitative with a focus on case studies. Data sources include primary and secondary data obtained through observation, interviews, and documentation. For data analysis, calculations were carried out on all elements of production costs, including raw material costs, direct labor costs, variable factory overhead costs, and fixed factory overhead costs using the Full Costing method. The research findings show that the total production cost according to the entrepreneur's calculations is Rp2,510,000, while based on the Full Costing method, the total reaches Rp1,689,003 with a difference of Rp820. 997. These results show that cost calculations carried out using the Full Costing method are more accurate, which makes it a basis for setting more appropriate selling prices and increasing efficiency in cost management in MSMEs.